The presence of partial compaction patterns is associated with lower rates of blastocyst formation, sub-optimal morphokinetic parameters and poorer morphologic grade - Christine Hur; Vaani Nanavaty; Meng Yao; Nina Desai (Reproductive Biology and Endocrinology, 2023)
Abstract Background Compaction is an important marker of embryonic genome activation and marks a critical step in the development to blastocyst. The objective of our study was to determine whether visualization of the embryonic compaction process through time-lapse imaging (TL) can assist in predicting the kinetics of embryo development as well as the likelihood for blastocyst formation, grade, or ploidy. Methods This study is a retrospective review of prospectively collected data from a single academic institution. Couples included were those who underwent preimplantation genetic testing for aneuploidy (PGT-A) following in vitro fertilization between January and December 2020. Embryos were cultured in the Embrysocope. Embryo morphokinetic data was prospectively collected and analyzed. TL videos were later reviewed in detail for compaction pattern. Embryo compaction patterns (CP) were categorized as follows: 1) full compaction (CP-F), 2) partial compaction with cell extrusion (P-ext), 3) partial compaction with cell exclusion (P-exc) and 4) partial compaction with both cell extrusion and exclusion (P-both). Assessment of embryo decompaction and re-compaction was evaluated. The association between CP, morphokinetic parameters, blastocyst formation, grade and ploidy were then analyzed. Results A total of 349 embryos were studied. Amongst embryos which progressed to morula (n = 281), the distribution of compaction patterns were: CP-F 45.6%, P-ext 12.5%, P-exc 29.5% and P-both 12.5%. Embryos exhibiting a CP-F were more likely to proceed to blastocyst compared with those that demonstrated partial compaction patterns (p = 0.006). When compared to CP-F, partial compaction patterns were significantly associated with poorer ICM and TE grades (P < 0.001). Of the 281 morula, 59.8% (n = 168) demonstrated at least one episode of decompaction and re-compaction. Of the 249 blastocysts formed, 200 were cryopreserved for future use after undergoing PGT-A evaluation. Of those, 42.5% were diagnosed as euploid, 39.0% as aneuploid, 9.0% as mosaic and 9.5% had no result. When compared to CP-F, partial CPs exhibited a significantly greater percentage of mosaic embryos (3.6% v. 15.6%, p = 0.032). Additionally, we found that a greater percentage of embryos demonstrating CP-F exhibited morphokinetics that fell into optimal ranges for embryo development when compared to those with partial compaction patterns. Conclusion Time-lapse visualization of compaction patterns identified exclusions and/or extrusions as negative indicators of blastocyst formation and blastocyst grade. When compared to full compaction patterns, partial compaction patterns were associated with delayed embryonic development as well as lower rates of optimal kinetic development.